THE ROLE OF AKHLAKUL KARIMA IN CURRICULUM DEVELOPMENT; BULLYING PREVENTION IN MADRASAH ALIYAH - Widiastuti, Sri; Fauzan, Hilman (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of the study is to determine whether there is an effect of implementing akhlakul karima in curriculum development to prevent bullying at school. In the implementation of the teaching and learning process, instilling good moral character in students is crucial to their development. Morals should be introduced and implemented as part of their daily routine at a young age to become a fundamental aspect of their lives. With the advancement of technology and the widespread influence of the internet, students are exposed to a variety of positive and negative information, which can easily influence their lives. By adhering to the right morals, students can filter out the negative influences and distinguish between good and bad, based on the teachings of their respective religions. The curriculum is subject to change with the changing times. One of its key objectives is to put on the practice of akhlakul karima in students' everyday life at school. The habit should start with the teachers, who should perform as facilitators and inspirers, whereas the school should support the process of nurturing good behavior in students through the curriculum. Recent instances of bullying highlight the students' inadequate comprehension of the significance of akhlakul karima. Islam teaches us to love and respect each other. As educational institutions, schools have a crucial role in teaching students. Therefore, the curriculum at school must include the cultivation of akhlakul karima, which emphasizes good character building. The research conducted qualitative research by content analysis in the Madrasah Aliyah Kota Tasikmalaya curriculum. Results of the research illustrate school that implements akhlakul karima in their curriculum have a positive effect on preventing bullying. Even though there is an indefinite remark in the curriculum by the government, the hidden curriculum in the vision and mission of the school will build the good moral character of students.